Inhibition of Peroxisome Proliferator-Activated Receptor Gamma Prevents the Melanogenesis in Murine B16/F10 Melanoma Cells. (28th August 2014) - Chen, Jiun-Han; Chang, Junn-Liang; Chen, Pei-Ru; Chuang, Yun-Ju; Tang, Shih-Tsang; Pan, Shwu-Fen; Lin, Tzer-Bin; Chen, Kang-Hua; Chen, Mei-Jung
Abstract : The purpose of this study was to investigate if PPARγ plays a role in the melanogenesis. B16/F10 cells were divided into five groups: control, melanin stimulating hormone (α -MSH), α -MSH+retinol, α -MSH+GW9662 (PPARγ antagonist), and GW9662. Cells in the control group were cultured in the Dulbecco's modified Eagle's medium (DMEM) for 48 hrs. To initiate the melanogenesis, cells in all α -MSH groups were cultured in medium containing α -MSH (10 nM) for 48 hrs. Cells were treated simultaneously with retinol (5  μ M) in the α -MSH+retinol group. Instead of retinol, GW9662 (10  μ M) was cocultured in the α -MSH+GW9662 group. Cells in the final group were cultured in the DMEM with GW9662. All the analyses were carried out 48 hours after treatments. The α -MSH was able to increase cell number, melanin production, and the activity of tyrosinase, the limiting enzyme in melanogenesis. These α -MSH-induced changes were prevented either by retinol or by GW9662. Further analyses of the activities of antioxidant enzymes including glutathione, catalase, and the superoxide dismutase (SOD) showed that α -MSH treatment raised the activity of SOD which was dependent on PPARγ level. According to our results, the α -MSH-induced melanogenesis was PPARγ dependent, which also modulated the expression of SOD.